2013
DOI: 10.1016/j.jfineco.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Peer choice in CEO compensation

Abstract: Current research shows that firms are more likely to benchmark against peers that pay their Chief Executive Officers (CEOs) higher compensation, reflecting self-serving behavior. We propose an alternative explanation: the choice of highly paid peers represents a reward for unobserved CEO talent. We test this hypothesis by decomposing the effect of peer selection into talent and selfserving components. Consistent with our prediction, we find that the association between a firm's selection of highly paid peers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
137
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(145 citation statements)
references
References 48 publications
5
137
3
Order By: Relevance
“…Consistent with the latter, the choice of highly-paid peers increases in the CEO's tenure (used as a proxy for entrenchment) and the busyness of a …rm's directors (the number of other boards they sit on), and is more prevalent if the CEO is also the chairman (Faulkender and Yang, 2010). In contrast, Albuquerque, Franco, and Verdi (2013) argue that the choice of highly-paid peers is a reward for CEO talent. They …rst calculate the pay di¤erence between actually chosen peers and a group of hypothetical peers matched on …rm characteristics.…”
Section: Peer Groupsmentioning
confidence: 86%
“…Consistent with the latter, the choice of highly-paid peers increases in the CEO's tenure (used as a proxy for entrenchment) and the busyness of a …rm's directors (the number of other boards they sit on), and is more prevalent if the CEO is also the chairman (Faulkender and Yang, 2010). In contrast, Albuquerque, Franco, and Verdi (2013) argue that the choice of highly-paid peers is a reward for CEO talent. They …rst calculate the pay di¤erence between actually chosen peers and a group of hypothetical peers matched on …rm characteristics.…”
Section: Peer Groupsmentioning
confidence: 86%
“…A potential explanation for this trend draws from the way in which companies benchmark the compensation of their CEOs (DiPrete, Eirich, and Pittinsky 2010, Faulkender and Yang 2013, Albuquerque, De Franco, and Verdi 2013, Pittinsky and DiPrete 2013. Compensation benchmarking involves the assembly of a group of peer firms that serves as a lens through which CEO compensation can be evaluated (Barsalou 1983, Podolny 2001, Smith and Chae 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The business media and some academic research Yang 2010, Pittinsky andDiPrete 2013) suggest that companies indeed have a tendency to select larger firms and better paid CEOs into their compensation peer groups. However, recent scholarship has questioned the validity of these claims (Bizjak et al 2008, Albuquerque et al 2013, Cadman and Carter 2013, Kim et al 2015. For example, Albuquerque et al (2013) compare reported peer groups to propensity score matched peer groups and conclude that although CEOs in reported peer groups are more generously compensated, the gap is accounted for by variation in CEO talent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations